Automated conveyor system for football quality checking - Muhammad Rusydi Muhammad Razif; S. A. H. J. Norazuan; Ili Najaa Aimi Mohd Nordin; Hairulazwan Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Many incidents happen in football matches such as injury, fight between team and ball out of game as whistle is blow. The worst case is where the ball exploded as the ball kick simultaneously from two opposite directions. To reduce problem in football matches and ensure the quality of the football match specification, this project is proposed a conveyor system for football quality checking, focusing on the ball size and weight measurement. In the conveyor system, a conveyor belt is introduced as a medium for conveying the ball, sensors to check the football specification and microcontroller to read the sensor input and produce output in term of motor control and measurement display. The conveyor system is made for checking the FIFA standard ball specification and it was built portably for easily carry and used in sport shop. The system could operate automatically, thus reducing to the need for worker. This project is expected to reduce injury in football match and also ensure the quality of the ball is guaranteed. For a standard football size measurement, the ball weight shows almost similar to the standard specification with 20g differences.